1989
DOI: 10.1212/wnl.39.3.368
|View full text |Cite
|
Sign up to set email alerts
|

Taxol produces a predominantly sensory neuropathy

Abstract: Taxol, a plant alkaloid with promise as an antineoplastic agent, produced a predominantly sensory neuropathy in 16 of 60 patients treated in two phase I trials. This neuropathy occurred only at taxol doses greater than 200 mg/m2. Symptoms typically started 1 to 3 days following treatment, beginning in the hands and feet simultaneously in most patients. Electrophysiologic data suggests both axonal degeneration and demyelination. This previously undefined neurotoxic neuropathy most likely results from taxol's un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
119
1
6

Year Published

1991
1991
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(133 citation statements)
references
References 0 publications
7
119
1
6
Order By: Relevance
“…Intermediate concentrations of paclitaxel were present in the sciatic nerve and spinal cord, possibly due to paclitaxel transport along the centrifugal and centripetal branches of the dorsal root ganglia neuron axons [9]. Paclitaxel induced neuropathy is probably due to dysfunctional microtubules in dorsal root ganglia, axons and Schwann cells [10,11]. In vivo studies have shown that direct injection of paclitaxel into the rat sciatic nerve causes the formation of unusual microtubule aggregates resulting in demyelination and loss of axoplasmic transport [10,11].…”
Section: Pathogenesis Of Paclitaxel-mediated Neuropathymentioning
confidence: 99%
See 2 more Smart Citations
“…Intermediate concentrations of paclitaxel were present in the sciatic nerve and spinal cord, possibly due to paclitaxel transport along the centrifugal and centripetal branches of the dorsal root ganglia neuron axons [9]. Paclitaxel induced neuropathy is probably due to dysfunctional microtubules in dorsal root ganglia, axons and Schwann cells [10,11]. In vivo studies have shown that direct injection of paclitaxel into the rat sciatic nerve causes the formation of unusual microtubule aggregates resulting in demyelination and loss of axoplasmic transport [10,11].…”
Section: Pathogenesis Of Paclitaxel-mediated Neuropathymentioning
confidence: 99%
“…Paclitaxel induced neuropathy is probably due to dysfunctional microtubules in dorsal root ganglia, axons and Schwann cells [10,11]. In vivo studies have shown that direct injection of paclitaxel into the rat sciatic nerve causes the formation of unusual microtubule aggregates resulting in demyelination and loss of axoplasmic transport [10,11].…”
Section: Pathogenesis Of Paclitaxel-mediated Neuropathymentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 On the other hand, neurotoxicity cannot be prevented nor treated, can last for months, and in severe cases it may cause irreversible nerve damage. 6,7 Neurotoxicity, which has become the dose-limiting toxicity of paclitaxel, exhibits substantial interindividual variability. This toxicity is dose-dependent and more frequent in weekly paclitaxel regimens, 8,9 in patients with diabetes, previous neurotoxic chemotherapy treatments and in patients with pre-existing neuropathies.…”
Section: Introductionmentioning
confidence: 99%
“…An important dose-dependent side-effect of cisplatin is the development of peripheral neuropathy, mainly affecting thick-fibre-mediated sensory qualities (Thompson et al, 1984;Roelofs et al, 1984;Gerritsen van der Hoop et al, 1990a;Vecht et al, 1991; Hilkens et al, 1994). Neuropathy has also been reported as a dose-dependent side-effect of treatment with paclitaxel (Taxol) (Lipton et al, 1989;Gerven et al, 1994). As expected, trials on combination chemotherapy of cisplatin and paclitaxel found a high incidence of peripheral neuropathy (Rowinsky et al, 1991;Rowinsky et al, 1993;Chaudhry et al, 1994).…”
mentioning
confidence: 99%